Prawdziwy sukces firmy jest dzieckiem wiedzy i informacji, ale przede wszystkim talentu jej twórcy i realizatora - Kiełczewski, Stanisław (Genuine Progress of Firm Is a Child of Knowledge and Information but First of All Talent of Its Creator and Executor, 2008)
Polish economic organizations, state and local authorities need strategic talents who should be discovered, developed and used. We are convicted on marginalization if we do not take this task. I try to prove this thesis. I also try to present how to increase this most valuable staff potential. Economic colleges, but particularly strategic management departments have in the realization of these tasks an important role to play.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 150-155